Antigen-dependent modulation of immune responses to antigen-Fc fusion proteins by Fc-effector functions - Richel, Elie; Wagner, Jannik T.; Klessing, Stephan; Di Vincenzo, Riccardo; Temchura, Vladimir; Überla, Klaus (Frontiers in Immunology, 2023)
Fc-fusion proteins have been successfully developed for therapeutic purposes, but are also a promising platform for the fast generation and purification of immunogens capable of inducing strong humoral immune responses in preclinical immunization studies. As the Fc-portion of immunoglobulins fused to an antigen confers functional properties of the parental antibody, such as dimerization, binding to Fc-receptors and complement activation, several studies reported that Fc-fusion proteins elicit stronger antigen-specific antibody responses than the unfused antigen. However, dimerization or half-life extension of an antigen have also been described to enhance immunogenicity. To explore the role of Fc-effector functions for the immunogenicity of fusions proteins of viral glycoproteins and Fc fragments, the HIV-1 gp120 and the RBD of SARS-CoV-2 were fused to the wild type muIgG2a Fc fragment or mutants with impaired (LALA-PG) or improved (GASDIE) Fc-effector functions. Immunization of BALB/c mice with DNA vaccines encoding gp120 -Fc LALA-PG induced significantly higher antigen-specific antibody responses than gp120 -Fc WT and GASDIE. In contrast, immunization with DNA vaccines encoding the RBD fused to the same Fc mutants, resulted in comparable anti-RBD antibody levels and similar neutralization activity against several SARS-CoV-2 variants. Thus, depending on the antigen, Fc-effector functions either do not modulate or suppress the immunogenicity of DNA vaccines encoding Fc-antigen fusion proteins.